Childhood maltreatment, exercise and transition to bipolar disorder among major depressive disorder patients - Xiaojuan Zhang; Yuhua Liao; Xue Han; Guangduoji Shi; Wanxin Wang; Lan Guo; Yuancheng He; Yanzhi Li; Huimin Zhang; Hao Zhao; Yan Chen; Xuedie Sun; et al. (Translational Psychiatry)
Abstract Early and accurate identification and management of bipolar disorders (BDs) among major depressive disorders (MDDs) in clinical practice would place these patients in progressive early-onset bipolar care. The associations between childhood maltreatment, exercise and transition from MDD to BD remain unclear. To determine whether MDD patients reporting childhood maltreatment are at an increased risk of transition to BD. The secondary objective is to evaluate the moderating effects of exercise on the association. This prospective cohort study with a maximum follow-up of four years was based on the Depression Cohort in China. 1392 MDD with 18–65 years of age were enrolled between March 2019 and November 2023 after diagnosis by trained psychiatrists using the Mini-International Neuropsychiatric Interview and 1034 with complete data were finally included in the primary analysis. The Childhood Trauma Questionnaire-Short Form and exercise were collected at baseline, and clinician referrals for BD were confirmed at follow-up. Of the 1034 MDD patients included, the mean(SD) age was 28.32(7.00) years, and 714(69.1%) were women. 58 transitions to BD (39.64 per 1000 person years) were reported among MDD patients. Childhood emotional abuse (aHR, 1.05; 95%CI, 1.00–1.11; P = 0.04) and sexual abuse (aHR, 1.15; 95%CI, 1.04–1.27; P = 0.008) were positively associated with transition to BD. Stratified analyses showed that childhood emotional abuse (aHR, 1.08; 95%CI, 1.02–1.14; P = 0.007) was associated with transition to BD among patients without habitual exercise, but not among those with habitual exercise. Childhood emotional abuse and sexual abuse may be significant risk factors for the transition from MDD to BD, while exercise may partly offset the risk effects of emotional abuse and this transition. MDD patients who reported related childhood maltreatment, their families and health professionals should monitor closely and screen frequently for the possible emergence of BD.